GE_GERICHTE P/414/2019 vom 4. Februar 2025 - GE Cour de justice (2025)
ORDONNANCE PÉNALE;OPPOSITION(PROCÉDURE);RETRAIT(VOIE DE DROIT);FICTION;NOTIFICATION PAR VOIE OFFICIELLE | CPP.354; CPP.88; CPP.356; CPP.3